Apakah Leverage Dan Reputasi Auditor Berperan Dalam Opini Audit Going Concern? - Widyantari, Ida Ayu Made Dwi; Sokarina, Ayudia; Waskito, Iman (Jurnal Riset Mahasiswa Akuntansi, 2024)
This research aims to predict the role of profitability, leverage, auditor reputation, and previous year's opinion on going concern audit opinion . The type of research used is associative research with a quantitative approach. Testing was carried out on 18 manufacturing companies registered on the IDX for the 2017-2021 period using a logistic regression analysis model where the dependent variable value used a dummy variable. The results showed that profitability had a negative effect on the going concern audit opinion, the previous year's opinion had a positive effect on the going concern audit opinion, while the auditor's leverage and reputation did not affect the going concern audit opinion. The implication of this research is that it is important for investors and potential investors to consider the level of profitability because the higher the levelof profitability offered, the higher the level of profitability offered. The higher the profits that will be obtained by the holders and the previous year's auditor's opinion will be used as a basis for decision making because the opinion received by the company is proven to be one of the important pieces of information that describes the performance of the company concerned.